Countering Discourses of Derision: Moving towards Action in Teacher Education in the USA and Sweden - Katarina Blennow; Martin Malmström; Elizabeth Petroelje Stolle (MDPI AG, 2023)
This article is about how negative discourses of teacher education position teacher educators and how they might influence or inspire action. We use self-study methods to investigate the political dimension of teacher education in two national contexts: Sweden and the USA. More specifically, we examine the emotions stirred by the positioning related to being a teacher educator and how those emotions can be used to take a line to and resist boundaries that limit us within the profession in the two contexts. We aim to contribute to the self-study field by emphasizing a political dimension, in addition to the personal and professional dimensions of teacher education more often studied by scholars. Using the concepts of positionality, emotions, liminality, and action, we conclude that the liminal spaces offered us time to think about the emotions we have experienced due to the derisive discourses that position us in negative ways as teacher educators, and with that thinking came opportunities to reflect on our identity as teacher educators and what we look to accomplish as teacher educators. A new understanding of liminality as a space of possibility has boosted us to take action. An important conclusion is that emotional labor can be a hindrance in relation to teacher educator action, while emotions can act as clues for opportunities of growth and action. Telling our stories opened space for us to use our emotions to take a line to and resist the derogatory discourse, engage in the political, and move closer to becoming teacher educator activists.